Transparency in Portuguese local government: A study of its determinants - Nuno Ribeiro; Sónia Nogueira; Ivone Freitas (European Financial and Accounting Journal, 2017)
Transparency of public management is fundamental to bringing citizens closer to public managers and as such universally considered an element of good governance. The main aim of this study is to identify the factors determining transparency in public management of Portuguese local authorities. Using the Municipal Transparency Index of 2013 and 2014, socio-demographic, political and economic-financial variables are studied for the population of 308 Portuguese local authorities by the means of testing the previously formulated research hypotheses in the light of the agency theory. The results show that transparency in public management of Portuguese local authorities is determined by their size, the number of individuals aged between 15 and 74 who use the internet, unemployment rate, financial autonomy and the net debt.
Keywords: H11; H70; H72; 650; Accountability; Local Authorities; Transparency